Outcomes of Stereotactic Body Radiotherapy for Metastatic Colorectal Cancer With Oligometastases, Oligoprogression, or Local Control of Dominant Tumors - Ji, Xiaoqin; Zhao, Yulu; Zhu, Xixu; Shen, Zetian; Li, Aomei; Chen, Cheng; Chu, Xiaoyuan (Frontiers in Oncology, 2021)
Abstract: Aim To evaluate the clinical outcomes of metastatic colorectal cancer (mCRC) patients with oligometastases, oligoprogression, or local control of dominant tumors after stereotactic body radiotherapy (SBRT) and establish a nomogram model to predict the prognosis for these patients. Methods and Materials A cohort of 94 patients with 162 mCRC metastases was treated with SBRT at a single institution. Treatment indications were oligometastases, oligoprogression, and local control of dominant tumors. End points of this study were the outcome in terms of progression-free survival (PFS), overall survival (OS), local progression (LP), and cumulative incidence of starting or changing systemic therapy (SCST). In addition, univariate and multivariable analyses to assess variable associations were performed. The predictive accuracy and discriminative ability of the nomogram were determined by concordance index (C-index) and calibration curve. Results Median PFS were 12.6 months, 6.8 months, and 3.7 months for oligometastases, oligoprogression, and local control of dominant tumors, respectively. 0-1 performance status, < 10 ug/L pre-SBRT CEA, and ≤ 2 metastases were significant predictors of higher PFS on multivariate analysis. Median OS were 40.0 months, 26.1 months, and 6.5 months for oligometastases, oligoprogression, and local control of dominant tumors, respectively. In the multivariate analysis of the cohort, the independent factors for survival were indication, performance status, pre-SBRT CEA, and PTV, all of which were selected into the nomogram. The calibration curve for probability of survival showed the good agreement between prediction by nomogram and actual observation. The C-index of the nomogram for predicting survival was 0.848. Conclusions SBRT for metastases derived from colorectal cancer offered favorable survival and symptom palliation without significant complications. The proposed nomogram could provide individual prediction of OS for patients with mCRC after SBRT.